Sistem Informasi Pariwisata Di Kota Wisata Batu Berbasis Android - Riza Ari Pratama; Noven Indra Prasetya; Emmy Wahyuningtyas (Melek IT : Information Technology Journal, 2015)
Tourism activity has existed since the journey from one place to another. The need for a trip and need to be fulfilled. Motivation or motif of travel is different, according to the economic and environmental communities themselves and in accordance with the level of development of their cultural and social levels. The data obtained in the study of literature sources and observations, analyzing the needs of the few tourist attractions and lodging in the city of stone. This application design using the Unified Modeling Language (UML) to manufacture android based application programming blog. The information systems provide a draft proposal of travel planning information applications. Where these systems can guide tourists when it will conduct traveled so tourists can independently determine travel planning without the help of a tour guide or a tourism agency. tourists can estimate the cost of the tour, as well as get information about routes and transportation to get to the tourist attractions and lodging.